Development of a Lateral Flow Immunoassay Test Strip for the Rapid Detection of Rubella Virus - Truong, Quoc Phong; Nguyen, Thi Anh Hoa; Ngo, Thu Huong; Pham, Huong Giang; Khuat, Huu Thanh (Old Journal, 2018)
This study was designed to construct a lateral flow immunoassay test strip for rapid detection of rubella virus. Rabbit anti-rubella antibody and pig anti-rubella antibody were successfully purified from sera of rabbit and pig infected with rubella virus. The yields of IgG affinity purification were 1.74 mg/ml and 3.23 mg/ml serum, respectively. Suitable conditions for conjugation of antibody and gold nanoparticles (AuNPs) were determined: 0.5 μg rabbit anti-rubella antibody was conjugated with 10 μl of AuNPs at pH 10, 37°C for 90 min. Similarly, suitable conditions for immobilization of pig anti-rubella antibody on the nitrocellulose were 3 μg of antibody, nitrocellulose membrane of Pall Vivid 170, immobilizing buffer of 20 mM sodium borate plus 2% sucrose, at 37°C for 30 min. The complete test strip was successfully constructed for rapid detection of rubella virus.